Physicochemical Evaluation of River Taraba at Bali, Taraba State, Nigeria: Comparison with World Health Organization Drinking Water Standard - Mohammed Hammajam (INTERNATIONAL JOURNAL OF CHEMISTRY AND CHEMICAL PROCESSES, 2026)
In Bali Local Government Area, Taraba State, Nigeria, River Taraba functions as an indispensable source of water for household use, agricultural irrigation, and fisheries. The present investigation quantified key physicochemical parameters pH, total hardness, total dissolved solids, nitrate, and phosphate in the riverine system and benchmarked the results against the World Health Organization’s drinking-water quality guidelines Ibrahim, et-al (2018). Samples were collected from three sites in January 2026 and analyzed using APHA standard methods. The average results were pH 8.10, hardness 68.67 mg/L CaCO₃, TDS 76.67 mg/L, nitrate 4.06mg/L, and phosphate 0.24 mg/L. All parameters fell within world Health Organization (WHO) permissible limits, suggesting the water is suitable for domestic and agricultural use based on the assessed characteristics. Low nutrient concentrations indicate minimal contamination during the dry season. > Nevertheless, intensification of farming activities upstream has the potential to elevate nutrient inputs during the wet season. To preserve water quality, ongoing surveillance and public awareness initiatives on proper waste disposal are advised. The findings provide baseline data for environmental management and public health planning in the region.